MASCULINO 21 AÑOS CON CUADRO SÚBITO DE DEBILIDAD, MIALGIAS Y CPK MAYOR A 400.000 UI/L - Méndez Rodríguez, Juan Diego (2011)
After physical exertion, the patient was admitedto the hospital with clinical and laboratoryfindings compatible with a clinical syndrome ofrhabdomyolysis, which main cause is an abnormal release of intracellular muscularcomponents, mainly creatine kinasa, into theblood flow, leading to metabolic, kidney andheart complications. Still, it is necessary toperform an focused clinical history to achieve athorough analysis that can help us to make anadequate diagnostic and therapeutic approach.